Does Aid for Trade Matter for Lesotho’s Exports? - Siyakiya, Puruweti; Mohatonyana, Letsie; Alotsi, Boithatelo; Makintane, Nkopelo; Molise, Keneuoe; Lethaane, Relebohile Precious (International Journal of Economics and Financial Issues, 2025)
Sub-Saharan African (SSA) countries face severe economic challenges, particularly low economic growth rates, high trading costs, infrastructure deficits, and poor trade performance. Lesotho is no exception; thus, development assistance is key to overcoming these challenges. SSA countries are among the highest recipients of aid for trade (AfT), with a rising share of AfT globally. Lesotho’s share of AfT has been rising, as has its trade; hence, it is necessary to establish whether AfT impacts Lesotho’s export performance. This study analyzes the impact of bilateral AfT from selected seven (7) countries to Lesotho on Lesotho’s exports from 2002 to 2022. This study uses the gravity model of trade, and precisely, it applies Poisson Pseudo Maximum Likelihood (PPML). The results show that AfT and the other variables that affect export performance have a statistically significant impact on Lesotho’s exports. Specifically, a dollar increase in AfT significantly leads to an increase in Lesotho’s exports, on average, ceteris paribus. Therefore, Lesotho’s export performance may be further enhanced by maintaining and increasing its aid for trade programs, which will increase competitiveness, make targeted investments in important industries, launch capacity–building programs, and ease trade restrictions. In this regard, AfT should be used for trade facilitation by building trade-related infrastructure, building the capacity of the agencies involved in the formulation of trade policies, and creating a conducive trading environment. Addressing these issues will go a long way to reducing trade costs and improving supply chain efficiency.